Crisis Communication and Sustainability Strategy of PT Kereta Api Indonesia: A Case Study of The 2026 Bekasi Timur Train Tragedy - Delli Asterina; Easter Tobing (Edunity Kajian Ilmu Sosial dan Pendidikan, 2026)
Public transportation organizations face significant reputational risks when major crises involving human casualties occur. As a state-owned railway company, PT Kereta Api Indonesia (KAI) must manage not only operational recovery but also public trust, stakeholder expectations, and long-term sustainability commitments following a crisis. This study aimed to examine the crisis communication and sustainability strategies implemented by KAI in responding to the 2026 East Bekasi train tragedy, focusing on situation analysis, stakeholder management, communication strategies, media utilization, and CSR/ESG-based reputation recovery. This research employed a qualitative approach with a single-case study design. Data were collected from secondary sources, including official KAI publications, verified national media reports, National Transportation Safety Committee (KNKT) investigation documents, and public records related to crisis management. Data analysis was conducted using Situational Crisis Communication Theory (SCCT), SWOT analysis, stakeholder mapping, and the AMEC communication evaluation framework. The findings indicated that KAI’s crisis response effectiveness was supported by rapid communication protocols, transparent information disclosure, empathetic messaging, strategic media utilization, and collaboration with external stakeholders. CSR and sustainability communication also contributed to rebuilding public confidence by emphasizing victim assistance, safety improvements, and governance transparency. This study concluded that integrated crisis communication combined with sustainability-oriented strategies could strengthen organizational resilience and reputation recovery. Future research should incorporate primary data and quantitative measurements to validate stakeholder perceptions and evaluate long-term reputation outcomes.